Functional Status of Pancreatic α and β Cells in Type 2 Diabetes Mellitus Patients with Different Plasma Triglyceride Levels: A Retrospective Analysis - Hang Guo; Chunlei Ma; Xiaoming Wu; Congqing Pan (International Journal of Endocrinology)
Objective. To investigate the functional status of pancreatic α and β cells in Type 2 diabetes mellitus (T2DM) patients with different plasma triglyceride (TG) levels. TG levels can be prognostic markers for T2DM. Methods. A total of 328 patients with T2DM were divided into three groups according to different TG levels: the TGL group: TG < 1.7 mmol/L; TGM group: 1.7 mmol/L ≤ TG < 2.3 mmol/L; and TGH group: TG ≥ 2.3 mmol/L. An oral glucose tolerance test (OGTT), insulin release test, and glucagon release test were performed in each patient. The changes of glucagon, glucagon/insulin ratio, early insulin secretion index (ΔI30/ΔG30), and area under the insulin curve (AUCI) were compared among each group. Also, the correlations between glucagon and pancreatic β-cell function, glycosylated hemoglobin (HbA1c), and other indices were analyzed. Results. With the increase of TG, the fasting and postprandial glucagon levels, the glucagon/insulin ratio, and the area under the glucagon curve (AUCG) presented an increasing trend. The homeostasis model assessment of insulin resistance (HOMA–IR) of the TGH group was significantly increased compared to the TGL and TGM groups. In addition to the increase in TG levels, the insulin sensitivity index (ISI), homeostasis model assessment for β-cell function index (HOMA-β), ΔI30/ΔG30, and AUCI displayed a reducing trend. Glucagon was negatively correlated with ΔI30/ΔG30, high-density lipoprotein (HDL), HOMA-β, body mass index (BMI), ISI, and AUCI (P<0.05) and positively correlated with fasting blood glucose (FPG), AUCG, HOMA-IR, HbA1c, duration, TG, low-density lipoprotein (LDL), and total cholesterol (TC) (P<0.05). Conclusion. Hypertriglyceridemia aggravated the dysfunction of pancreatic α and β cells. A reasonable control of the TG level makes it easier for blood glucose to reach the standard.